Bovine Serum Albumin-Glutaraldehyde Sealed Fish-Mouth Closure of the Pancreatic Remnant during Distal Pancreatectomy - Klein, Fritz (HPB Surg, 2017)
Introduction. Postoperative pancreatic fistula formation remains the major complication after distal pancreatectomy. At our institution, we have recently developed a novel bovine serum albumin-glutaraldehyde sealed hand sutured fish-mouth closure technique of the pancreatic remnant during distal pancreatectomy. The aim of this study was to analyze the impact of this approach with regard to technical feasibility and overall postoperative outcome. Patients and Methods. 32 patients who underwent a bovine serum albumin-glutaraldehyde sealed hand sutured fish-mouth closure of the pancreatic remnant during distal pancreatectomy between 2012 and 2014 at our institution were analyzed for clinically relevant postoperative pancreatic fistula formation (Grades B and C according to ISGPF definition) and overall postoperative morbidity. Results. Three out of 32 patients (9.4%) developed Grade B pancreatic fistula, which could be treated conservatively. No Grade C pancreatic fistulas were observed. Postpancreatectomy hemorrhage occurred in 1 patient (3.1%). Overall postoperative complications > Clavien II were observed in 5 patients (15.6%). There was no postoperative mortality. Conclusion. The performance of a bovine serum albumin-glutaraldehyde sealed hand sutured fish-mouth closure of the pancreatic remnant was shown to be technically feasible and may lead to a significant decrease of postoperative pancreatic fistula formation after distal pancreatectomy.